PTMs of PD-1/PD-L1 and PROTACs application for improving cancer immunotherapy - Ren, Xiaohui; Wang, Lijuan; Liu, Likun; Liu, Juan (Frontiers in Immunology, 2024)
Immunotherapy has been developed, which harnesses and enhances the innate powers of the immune system to fight disease, particularly cancer. PD-1 (programmed death-1) and PD-L1 (programmed death ligand-1) are key components in the regulation of the immune system, particularly in the context of cancer immunotherapy. PD-1 and PD-L1 are regulated by PTMs, including phosphorylation, ubiquitination, deubiquitination, acetylation, palmitoylation and glycosylation. PROTACs (Proteolysis Targeting Chimeras) are a type of new drug design technology. They are specifically engineered molecules that target specific proteins within a cell for degradation. PROTACs have been designed and demonstrated their inhibitory activity against the PD-1/PD-L1 pathway, and showed their ability to degrade PD-1/PD-L1 proteins. In this review, we describe how PROTACs target PD-1 and PD-L1 proteins to improve the efficacy of immunotherapy. PROTACs could be a novel strategy to combine with radiotherapy, chemotherapy and immunotherapy for cancer patients.